LEGAL PROTECTION OF INDONESIAN CITIZENS WHO CONDUCT MARRIAGE WITH FOREIGN CITIZENS RELATED TO THE ACQUISITION OF LAND RIGHTS - Sisi Widya Putri; Ismail Ismail (The Juris, 2023)
The official bond in marriage between Indonesian citizens and foreign nationals is sustained through direct interactions. The union of Indonesian citizens and foreign citizens in Indonesia is commonly referred to as Mixed Marriages. The present study employs a normative juridical research approach, specifically relying on library law research or secondary data, which draws upon primary, secondary, and tertiary legal sources. The study employed a research methodology that incorporated the use of statutory, conceptual, and case-based approaches. The process of collecting legal materials involved the identification and inventorying of advantageous legal regulations, literary publications, academic journals, and other relevant sources of legal information. The analysis of legal materials is conducted through the application of grammatical and systematic interpretation techniques. The research findings indicate that the implementation of legal regulations pertaining to land rights in mixed marriages without a marriage agreement has undergone changes following the ratification of Constitutional Court Decision Number 69/PUU-XIII/2015. This has resulted in modifications to the provisions outlined in Article 29 paragraphs (1) to (4) of The Marriage Law, which now offer legal protection to Indonesian citizens who engage in mixed marriages with foreigners and seek to obtain land rights. Specifically, in the absence of a marriage agreement, such a union can lead to the creation of joint assets. It is advisable for couples who engage in cross-cultural marriages to establish a matrimonial agreement that outlines the division of property between spouses. It is also important for Indonesian citizens to adhere to the legal provisions and regulations pertaining to such agreements, and to ensure that they have secured property ownership rights, particularly with regards to land